Children’s Understanding and Use of Intersectional Stereotypes - Jiao, Rujia (Wake Forest University, 2025)
Stereotypes based on race and gender emerge early in childhood, shaping children’s perceptions of social groups and leading to intergroup discrimination. Extensive previous research has examined children’s racial and gender stereotypes separately, however, few studies have explored children’s simultaneous use of multiple social categories to form intersectional stereotypes. The current study addresses this gap by examining whether children aged 6 to 10 years (N = 148; 56.8% girls, 43.2% boys, 59.8% white, 21.2% Asian, 7.6% Latinx, 6.1% Multiracial, 5.3% Black) hold intersectional stereotypes about six social groups differing in race and gender. The study specifically focuses on warmth and competence stereotypes due to their central role in predicting behaviors and attitudes across the lifespan (see Stereotype Content Model; Fiske et al., 2002). For each dimension, children completed a forced-choice task in which they viewed 15 pairs of faces representing different race-gender combinations and rated who was nice (warmth) or smart (competence) from each pair. Children applied various intersectional stereotypes such as rating white and Asian women as nicer than Black women, or viewing Asian men as more competent than Black or white men. Exploratory analyses revealed additional effects of age, children’s gender, and experimenter race. The current study demonstrated that by early elementary school, children can encode and functionally use multiple social categories together. Further, the current study identifies children’s endorsement of stereotypes and thus informs early bias interventions that promote more equitable social perceptions and interactions.
Keywords: Developmental Social Cognition; Intersectionality; Stereotypes